(untitled) (Analysis in Theory and Applications, 2014)
In this paper, we study the existence of standing waves of the coupled nonlinear Schrödinger equations. The proofs of which rely on the Lyapunov-Schmidt methods and contraction mapping principle are due to F. Weinstein in [1].